Еlectret properties of γ-irradiated composites of ultrahigh molecular weight polyethylene/α-SiO₂ - Magerramov, A.M.; Ismayilova, R.S.; Kuliev, M.M.; Nabiev, A.A.; Gadzhieva, E.G.; Ismayilov, J.I.; Abdullaev, R.S.; Akhundova, G.A. (Вопросы атомной науки и техники, 2018)
The influence of silicon dioxide (α-SiO₂) and the absorbed dose of γ-irradiation on the electret properties of UHMWPE+α-SiO₂ composites were studied. It is established that the dependence of the stabilized charge on the volume content of the α-SiO₂ filler has an extreme character: at 1% α-SiO₂, the charge reaches a maximum and then decreases. TSD spectra show that the thermalstability of electrets of the UHMWPE+1 vol.% α-SiO₂ composite is improved. The nature of the TSD current of the films which preliminarily γ-irradiated up to 50…100 kGy doses proves that after γ-irradiation the charges injected from corona discharge zone are mainly accumulated in the subsurface layers. However, the deterioration of the electret properties of composites irradiated at high doses of γ-irradiation is related both to an increase in electrical conductivity so, and an increase in the rate of charge relaxation. Вивчено вплив діоксиду кремнію (α-SiO₂) і поглинутої дози γ-опромінення на електретні властивості композитів надвисокомолекулярного поліетилену (НВМПЕ)+α-SiO₂. Встановлено, що залежність стабілізованого заряду від об'ємного вмісту наповнювача α-SiO₂ має екстремальний характер: при 1% α-SiO₂ заряд досягає максимуму, а потім зменшується. На основі аналізу спектрів ТСД показано, що поліпшується термостабільність електретів з композиту НВМПЕ+1% α-SiO₂. Характер струму ТСД попередньо γ-опромінених до доз 50...100 кГр плівок доводить, що після γ-опромінення інжектовані із зони корони заряди в основному накопичуються в приповерхневих шарах. Погіршення електретних властивостей попередньо γ-опромінених композитів пов'язано як з підвищенням електропровідності, так і зі зростанням швидкості релаксації зарядів. Изучены влияния диоксида кремния (α-SіО₂) и поглощенной дозы γ-облучения на электретные свойства композитов сверхвысокомолекулярного полиэтилена (СВМПЭ)+α-SіО₂.. Установлено, что зависимость стабилизированного заряда от объемного содержания наполнителя α-SіО₂ имеет экстремальный характер: при 1% α-SіО₂ заряд достигает максимума, а затем уменьшается. На основе анализа спектров ТСД показано, что улучшается термостабильность электретов из композита СВМПЭ+1% α-SіО₂. Характер тока ТСД предварительно γ-облученных до доз 50…100 кГр пленок доказывает, что после γ-облучения инжектированные из зоны короны заряды в основном накапливаются в приповерхностных слоях. Ухудшение электретных свойств предварительно γ-облученных композитов связано как с повышением электропроводности, так и с возрастанием скорости релаксации зарядов.